Compensatory mechanism involving the knee joint of the intact limb during gait in unilateral below-knee amputees - Beyaert, C.; Grumillier, C.; Martinet, N.; Paysant, J.; André, J.-M. (Gait & posture, 2008)
This study evaluated the asymmetry of knee kinetics during uncomfortable gait induced by prosthesis misalignment to further demonstrate the compensatory function of the knee joint of the intact limb during gait. Three-dimensional gait analysis including knee kinematics and kinetics at the beginning of stance phase was conducted in 15 healthy subjects and 17 unilateral trans-tibial amputees (TTA) walking at self-selected speed in three conditions of prosthetic alignment: initial alignment (IA); initial alignment altered either by 6° of internal rotation (IR) or by 6° of external rotation (ER) applied on the pylon. Patients reported best comfort of gait in IA condition and discomfort mainly in IR condition. Maximum knee flexion and knee total work at power phases K0–K2 were significantly higher in intact limbs compared to prosthetic and control limbs. In intact limbs, these variables had significantly higher values (+10–35%, p < 0.05) in IR condition than IA condition whereas these were not altered across conditions in prosthetic limbs. In trans-tibial amputees, inducing uncomfortable gait by internally rotating the prosthetic foot did not alter the knee kinetics of the prosthetic limb, which suggests a protective mechanism. Knee kinetics of the intact limb did alter, which suggests a compensatory mechanism.